Physical and chemical characterization of organic wastes with potential use as components of horticultural substrates (Bioagro, 2024)
In recent decades, interest has been generated in integrating agro-industrial and harvest residues into agricultural production in intensive production systems, to reduce environmental impact and production costs. Therefore, the objective of this research was to chemically and physically characterize some locally available agro-industrial and vegetable residues to know their potential use as components of agricultural substrates. Chemical and physical properties of organic materials were characterized: pH and EC, granulometry, average particle diameter, bulk density (Bd), total porosity (Tp), aeration porosity (Ap), water retention porosity (Wp), and moisture retention curves were determined. The pH of the analyzed materials ranged from 5.1 to 10.44, the CE was lower than 2 dS·m-1 except for the water lily and banana rachis fiber. The granulometry of the materials had more than 25 % of particles smaller than 0,85 mm; however, the teak shavings and the husk of the oil palm fruit had a Pd with 5.67 mm and 3.21 mm, respectively, which increased their aeration capacity. Pine sawdust and cocoa fruit husk had values ​​higher than the control in Bd, Tp, Ap, Wp and total available water. In conclusion, the materials have different aeration and moisture retention characteristics, and they can be combined in different proportions according to their physical and hydrophysical characteristics and generate a balance in the water-air relationship.
Keywords: Agro-industrial oil palm residues; banana rachis; cocoa husk; water lily; wood sawdust